Evaluating the reinvention of the movie theatre experience and its role in building brand equity in the new digital age - Da Silva, Christine (The IIE, 2020)
Ster-Kinekor has remained relevant despite the despite the vast change in technology and innovation; the brand remains valuable to moviegoers and the organisation itself (Bratt, 2019). The main argument this research study presents is whether this justifies Ster-Kinekor’s relevance in the new digital age. This is approached by unpacking Ster-Kinekor’s movie theatre experience with the aim to understand how Ster-Kinekor’s movie theatre experience ensures that positive feelings are linked to the brand and through this determining how this contributes to brand equity. The researcher made use of qualitative research methods such as interviews and focus group, as part of the field research to gather data. While of thematic content analysis was used as a type of qualitative data analysis technique organizing, describing, and extracting themes found within the data gathered. The main findings reveal that moviegoers place customer experience and shared experience as the top two reasons why movie going at Ster-Kinekor is preferred while the brand places emphasis on their technology, innovation, and loyalty programmes. The research concludes that Ster-Kinekor’s efforts are aligned to moviegoer’s preferences when it comes to seeking a sense of escapism and shared experiences.
Keywords: Technology; Innovation; Customer experience; Loyalty programmes; Streaming services; Cinema industry; Keller's Brand Equity Model